2022
DOI: 10.1002/ange.202211112
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of Heparan Sulfate Oligosaccharides having a Domain Structure**

Abstract: Heparan sulfate (HS) has a domain structure in which regions that are modified by epimerization and sulfonation (NS domains) are interspersed by unmodified fragments (NA domains). There is data to support that domain organization of HS can regulate binding of proteins, however, such model has been difficult to probe. Here, we report a chemoenzymatic methodology that can provide HS oligosaccharides composed of two or more NS domains separated by NA domains of different length. It is based on the chemical synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…263 Very recently, Sun, Chopra and Boons reported a chemoenzymatic synthesis of an HS-like polysaccharide assembled from highly sulfated and undersulfated components, achieving "domains" of different sulfation, like natural HS. 266 Six days later, Baryal et al reported the development of a library of 64 synthetically prepared tetrasaccharides, from which was identified a high FGF2-binding molecule with low platelet factor-4 binding. 267 Assuming this binding translates into potentiation of useful biological activity, this approach is promising for the elucidation and generation of BMP2 potentiating glycosaminoglycans.…”
Section: 7: Summary and Relevance Of 18f Bioassay Datamentioning
confidence: 99%
“…263 Very recently, Sun, Chopra and Boons reported a chemoenzymatic synthesis of an HS-like polysaccharide assembled from highly sulfated and undersulfated components, achieving "domains" of different sulfation, like natural HS. 266 Six days later, Baryal et al reported the development of a library of 64 synthetically prepared tetrasaccharides, from which was identified a high FGF2-binding molecule with low platelet factor-4 binding. 267 Assuming this binding translates into potentiation of useful biological activity, this approach is promising for the elucidation and generation of BMP2 potentiating glycosaminoglycans.…”
Section: 7: Summary and Relevance Of 18f Bioassay Datamentioning
confidence: 99%